Optimasi Produksi Berbasis Web Dengan Metode Linear Programming: Studi Kasus Indutri Kecil dan Menengah - Nurachmad, Edi; Tsakila, Dziqri Qaulan; Cahyadi, Septian (Jurnal Aplikasi Bisnis Kesatuan, 2024)
CV Isna Sejati, a manufacturing company that focuses on the production of wooden doors and windows, faces challenges in terms of production efficiency. The main problems faced are inefficient management of raw materials, less than optimal production capacity planning, and inaccurate cost estimates. This condition causes increased production costs and decreases profitability, thus hampering the growth and competitiveness of the company in the market. This study aims to develop a web-based production optimization calculator as a solution to the problems faced by SMEs, especially the manufacturing industry. This calculator is designed to improve production efficiency by managing raw materials better, planning production capacity effectively, and providing accurate cost estimates. Optimization algorithms and mathematical methods are used in this calculator to help companies set more effective and efficient production plans. The results of implementing the production optimization calculator show an increase in operational efficiency in the company. The use of raw materials becomes more efficient, the distribution of work between employees is more even, and production time can be allocated better. In addition, more accurate cost estimates help companies manage budgets and resources more effectively.   Keywords: Production Optimization, Linear Programming, Small and Medium Industries, Manufacturing Industry.